KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI SISWA KELAS X MAN MANDAH KABUPATEN INDRAGIRI HILIR - Buhairah '; Auzar '; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a study about the ability on reading comprehension in Narrative text of the first year students of MAN Mandah Indragiri Hilir. This research aimed to know and describe the ability on reading comprehension in Narrative text of the first year students of MAN Mandah Indragiri Hilir. This research was quantitative descriptive. The data of this research was the results of the reading comprehension in narrative text test of the first year students of MAN Mandah Indragiri Hilir. The form of the instrument in this research was multiple choices which have five possible answers that related with the ability on reading comprehension in Narrative text of the first year students of MAN Mandah Indragiri Hilir. The data collecting technique was taken by test technique. The population in this research was 97 students while the sample was 71. The data was analyzed by quantitative descriptive thought Kruskall Wallis test. The validity was gotten by the data validation. The result of this research was sighted from the result of reading comprehension test of the first year students of MAN Mandah Indragiri Hilir. Based on the ability on reading comprehension in Narrative text of the first year students of MAN Mandah Indragiri Hilir was in very low category with the average score 40.81.Key words: Ability, Reading Comprehension, Narrative Text.